Blimp-1 Upregulation by Multiple Ligands via EGFR Transactivation Inhibits Cell Migration in Keratinocytes and Squamous Cell Carcinoma - Lee, Hyemin; Huang, Duen-Yi; Chang, Hua-Ching; Lin, Chia-Yee; Ren, Wan-Yu; Dai, Yang-Shia; Lin, Wan-Wan (Frontiers in Pharmacology, 2022)
B lymphocyte-induced maturation protein-1 (Blimp-1) is a transcriptional repressor and plays a crucial role in the regulation of development and functions of various immune cells. Currently, there is limited understanding about the regulation of Blimp-1 expression and cellular functions in keratinocytes and cancer cells. Previously we demonstrated that EGF can upregulate Blimp-1 gene expression in keratinocytes, playing a negative role in regulation of cell migration and inflammation. Because it remains unclear if Blimp-1 can be regulated by other stimuli beyond EGF, here we further investigated multiple stimuli for their regulation of Blimp-1 expression in keratinocytes and squamous cell carcinoma (SCC). We found that PMA, TNF-α, LPS, polyIC, H2O2 and UVB can upregulate the protein and/or mRNA levels of Blimp-1 in HaCaT and SCC cells. Concomitant EGFR activation was observed by these stimuli, and EGFR inhibitor gefitinib and Syk inhibitor can block Blimp-1 gene expression caused by PMA. Reporter assay of Blimp-1 promoter activity further indicated the involvement of AP-1 in PMA-, TNF-α-, LPS- and EGF-elicited Blimp-1 mRNA expression. Confocal microscopic data indicated the nuclear loclization of Blimp-1, and such localization was not changed by stimuli. Moreover, Blimp-1 silencing enhanced SCC cell migration. Taken together, Blimp-1 can be transcriptionally upregulated by several stimuli in keratinocytes and SCC via EGFR transactivation and AP-1 pathway. These include growth factor PMA, cytokine TNF-α, TLR ligands (LPS and polyIC), and ROS insults (H2O2 and UVB). The function of Blimp-1 as a negative regulator of cell migration in SCC can provide a new therapeutic target in SCC.